Competitive interaction in headwaters: slow upstream migration leads to trophic competition between native and non-native amphipods - Pelikan, Lars; Šidagytė-Copilas, Eglė; Garbaras, Andrius; Jourdan, Jonas; Copilaș-Ciocianu, Denis (Pensoft Publishers, 2025)
The spread of non-native species is one of the outcomes of global change, threatening many native communities through predation and competition. Freshwater ecosystems are particularly affected by species turnover with non-native species. One species that has been established in Central Europe for many decades – or even a few centuries – is the amphipod crustacean Gammarus roeselii. Although G. roeselii is nowadays widespread in major river systems, there have been recent reports of its spread into smaller streams that are typically inhabited by the native species Gammarus fossarum. Due to their leaf shredding ability, G. fossarum takes up a key position in headwater streams. This raises the important question, to what extent G. roeselii can equivalently take over this function. To answer this question, we collected both species from nine different sites in a mid-mountain river system (Kinzig catchment, Hesse, Germany) and investigated their functional similarity using a combination of stable isotope analysis, gut content and functional morphology. The species hardly differed in morphological characteristics, only females showed differences in some traits. Gut content analysis indicated a broad dietary overlap, while stable isotopes showed a higher trophic position of G. roeselii. The observed functional overlap could intensify interspecific competition and allow the larger and more predaceous G. roeselii to replace G. fossarum in the future as a headwater keystone species. However, the differentiation in the stable isotopes also shows that co-existence can occur by occupying different trophic niches. Moreover, the wide range of inhabited sites and exploited resources demonstrate the omnivorous lifestyle of G. roeselii, which is likely to help the species succeed in rapidly changing environments.